Number, density and sex−age of the moose Alces alces population in north−eastern Poland after 20 years of hunting ban ... : Liczebność, zagęszczenie i struktura płciowo−wiekowa populacji łosia Alces alces w objętej 20−letnim zakazem polowań północno−wschodniej Polsce ... - Bobek, Bogusław; Furtek, Jakub; Merta, Dorota; Wojciuch-Płoskonka, Marta (Polskie Towarzystwo Leśne, 2024)
The moose hunting ban in Poland resulted in a dramatic growth in population number which is now the cause of major damage to forests and farmlands and numerous traffic accidents. The lack of well−documented data pertaining to moose numbers constitutes the prime barrier to reopening the hunting season. In February 2020, the population density and number of moose were estimated in the Augustów Forest, a large (1120.0 km) forest complex in north−eastern Poland. Observations made by a 30−person research team recorded moose numbers in 20 sampling plots on 91.5 km of the total area. The average population density amounted to 1.22 ±0.19 moose/ km (X̅±SE), indicating that 1344 animals were living in the study area. In autumn, among 609 adults, the sex ratio was 1:1.17 in favour of females and the number of calves per 100 females was estimated as 71.3 individuals. In the 2001−2020 period, the number of moose in the study area increased from 211 to 1344 individuals. The annual finite population increase rate (em/em) ... : Sylwan 168 (4): 287-295 ...